Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The Role of Digital Competencies as a Mediating Variable in the Relationship between Organizational Agility and Achieving Institutional Excellence in Secondary Schools  in the Southern GovernoratesMr. Mohammed Ibrahim Abu Borhom2. The Role of School Leadership in Developing Creativity among Teachers of Basic Stage (Public schools in Tubas Province model)Mrs. Rawan Abd Alkareem Alghwanmeh3. The Effectiveness of an Electronic Training Program Using Collaborative Groups on Developing Teachers’ Teaching Competencies of Health and Physical Education at The Primary LevelMr. Nasser Mohammed Al-Quhaiz , Co-Prof. Rashid Mohammed Al-Jassas , Asst-Prof. Abdulaziz Abdullah Al-Fayez4. The Effect of an Educational Program Based on Self-Learning to Develop Digital Skills among Al-Aqsa University StudentsAsst-Prof. Hana Khalil Abu Mutlaq, Co-Prof. Omer Ahmed Ibrahim5. The effectiveness of the skill of producing mobile applications to enhancing 21st century skillsMrs. Hanan Mohammed Bahkali, Mrs. Saja Saed Al-Jadaani, Co-Prof. Lina Ahmad Al-Farrani6. Psychological stress and its relationship to social support among tenth and eleventh grade students during the selection of academic subjects in Sultanate of OmanMrs. Fatma Said Obaid Al-Abri, Prof. Ahmed Maad
Keywords: Journal of Educational and Psychological Sciences